Quantum Computing:An Environment for Intelligent Large Scale Real Application - Hassanien, Aboul Ella.; Elhoseny, Mohamed; Kacprzyk, Janusz; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book highlights practical quantum key distribution systems and research on the implementations of next-generation quantum communication, as well as photonic quantum device technologies. It discusses how the advances in quantum computing and quantum physics have allowed the building, launching and deploying of space exploration systems that are capable of more and more as they become smaller and lighter. It also presents theoretical and experimental research on the potential and limitations of secure communication and computation with quantum devices, and explores how security can be preserved in the presence of a quantum computer, and how to achieve long-distance quantum communication. The development of a real quantum computer is still in the early stages, but a number of research groups have investigated the theoretical possibilities of such computers.
Quantum information protocols for cryptography -- Applications of quantum mechanics in secure communication -- Different Architectures of Quantum Key Distribution Network -- Quantum Computing and Cryptography: An Overview -- Quantum Key Distribution over Multi-Point Communication System: An overview -- IPsec Multicast Architecture Based on Quantum Key Distribution, Quantum Secret Sharing and Measurement -- Multi-Parties Quantum Secure Direct Communication with Authentication -- Quantum cryptography, quantum communication, and quantum computer in a noisy environment.
Keywords: Computational intelligence; Big data; Artificial intelligence; Computational Intelligence; Big Data; Artificial Intelligence